Cover Image. Issue 3 (18th January 2022) - Moretto, Manuela; Silvestri, Erica; Zangrossi, Andrea; Corbetta, Maurizio; Bertoldo, Alessandra
Abstract : COVER ILLUSTRATION In this figure the two boxes display for the young (on the left) and old (on the right) subjects the T1‐weighted image of a representative subject and the three topmost likely transition probabilities between inferred functional dynamic brain states. Inside each circle the spatial pattern of mean BOLD activation within the state is represented. The values of the transition probabilities are reported above each arrow.